Randomized controlled trial on the skin toxicity of panitumumab in Japanese patients with metastatic colorectal cancer: HGCSG1001 study; J-STEPP. (February 2015) - Kobayashi, Yoshimitsu; Komatsu, Yoshito; Yuki, Satoshi; Fukushima, Hiraku; Sasaki, Takahide; Iwanaga, Ichiro; Uebayashi, Minoru; Okuda, Hiroyuki; Kusumi, Takaya; Miyagishima, Takuto; Sogabe, Susumu; Tateyama, Miki; et al.
ABSTRACT : Aim: We planned a randomized, open-label trial to evaluate differences between pre-emptive and reactive skin treatment for panitumumab (Pmab)-associated skin toxicities in Japanese patients with metastatic colorectal cancer.Patients & methods: Patients receiving third-line Pmab-containing regimens were randomized to pre-emptive or reactive treatment. The primary end point was the cumulative incidence of ≥grade 2 skin toxicities during 6 weeks. Retrospectively, a dermatologist reviewed skin toxicities, in a blinded manner.Results: A total of 95 patients were enrolled (pre-emptive: 47, reactive: 48). The primary end point was achieved (21.3 and 62.5% [risk ratio: 0.34; p < 0.001], for pre-emptive and reactive treatment, respectively). A similar trend was observed in central review.Conclusion: Pre-emptive skin treatment could reduce the severity of Pmab-associated skin toxicities in Japanese metastatic colorectal cancer patients.